Synthesis of Polymers Containing Potassium Acyltrifluoroborates (KATs) and Post‐polymerization Ligation and Conjugation. Issue 34 (15th July 2020) - Schauenburg, Dominik; Divandari, Mohammad; Neumann, Kevin; Spiegel, Christoph A.; Hackett, Thomas; Dzeng, Yi‐Chung; Spencer, Nicholas D.; Bode, Jeffrey W.
Abstract: We report the synthesis of monomers for atom‐transfer radical polymerization (ATRP) and a reversible addition‐fragmentation chain transfer (RAFT) agent bearing trifluoroborate iminiums (TIMs), which are quantitatively converted into potassium acyltrifluoroborates (KATs) after polymerization. The resulting KAT‐containing polymers are suitable for rapid amide‐forming ligations for both post‐polymerization modification and polymer conjugation. The polymer conjugation occurs rapidly, even under dilute (micromolar) aqueous conditions at ambient temperatures, thereby enabling the synthesis of a variety of linear and star‐shaped block copolymers. In addition, we applied post‐polymerization modification to the covalent linking of a photocaged cyclic antibiotic (gramicidin S) to the side chains of the KAT‐containing copolymer. Cellular assays revealed that the polymer–antibiotic conjugate is biocompatible and provides efficient light‐controlled release of the antibiotic on demand. Abstract : KAT o'nine tails : Post‐polymerization modification and ligation of polymers under aqueous conditions is achieved by incorporating potassium acyltrifluoroborates (KATs) at side chains or the polymer terminus. This enables the attachment of unprotected small molecules, chromophores, and peptide‐based drugs through rapid amide‐forming ligations of KATs in water. Direct ligation to other polymers enables the synthesis of linear and branched block copolymers.